Increased burden of rare protein-truncating variants in constrained, brain-specific and synaptic genes in extremely impulsively violent males with antisocial personality disorder - Mušálková, Dita; Přistoupilová, Anna; Jedličková, Ivana; Hartmannová, Hana; Trešlová, Helena; Nosková, Lenka; Hodaňová, Kateřina; Bittmanová, Petra; Stránecký, Viktor; Jiřička, Václav; Langmajerová, Michaela; Woodbury-Smith, Marc; et al. (Genes, brain and behavior, 2024)
The genetic correlates of extreme impulsive violence are poorly understood, and there have been few studies that have characterized a large group of affected individuals both clinically and genetically. We performed whole exome sequencing (WES) in 290 males with the life-course-persistent, extremely impulsively violent form of antisocial personality disorder (APD) and analyzed the spectrum of rare protein-truncating variants (rPTVs). Comparisons were made with 314 male controls and publicly available genotype data. Functional annotation tools were used for biological interpretation. Participants were significantly more likely to harbor rPTVs in genes that are intolerant to loss-of-function variants (odds ratio [OR] 2.06; p < 0.001), specifically expressed in brain (OR 2.80; p = 0.036) and enriched for those involved in neurotransmitter transport and synaptic processes. In 60 individuals (20%), we identified rPTVs that we classified as clinically relevant based on their clinical associations, biological function and gene expression patterns. Of these, 37 individuals harbored rPTVs in 23 genes that are associated with a monogenic neurological disorder, and 23 individuals harbored rPTVs in 20 genes reportedly intolerant to loss-of-function variants. The analysis presents evidence in support of a model where presence of either one or several private, functionally relevant mutations contribute significantly to individual risk of life-course-persistent APD and reveals multiple individuals who could be affected by clinically unrecognized neuropsychiatric Mendelian disease. Thus, Mendelian diseases and increased rPTV burden may represent important factors for the development of extremely impulsive violent life-course-persistent forms of APD irrespective of their clinical presentation.
Keywords: agrese; Aggression; asociální osobnost; genotyp; lidé; mozek; Antisocial Personality Disorder; Humans; Brain; Violence; Male; mužské pohlaví; Genotype; násilí